DETERMINATION OF BUTTER-PALM OIL SPREAD COMPOSITION USING METHODS OF THERMAL ANALYSIS - Budanina L.N.; Vereshchagin A.L.; Bychin N.V. (Техника и технология пищевых производств)
Taking into account an increasing scale of dairy product adulteration a wide range of modern and classical methods of examination are used to identify that the butter is real. Methods of thermal analysis are rarely used because it is necessary to pre-cool the samples to -100˚C. Of thermal methods of analysis for the study of fat, the method of differential scanning calorimetry (DSC) is used more often. Thermal gravimetric (TGA) and differential thermal (DTA) analyzes are rarely used. In this study, we investigated the possibility to recognize the composition of dairy-plant spreads by means of thermal analysis. The objects of investigation were six samples of imported, domestic and individually produced butter purchased in retail of the Altai Territory. For comparison, a sample of palm oil manufactured at "Zhirovoy Kombinat" ZAO was taken. Based on these studies, the following conclusions have been made: the methods of thermal analysis (DSC, TGA/DTA) allow qualitative identification of butter-palm oil mixture, but fluctuations in the fatacid composition of milk fat and interaction of palm oil with butter significantly limit the possibilities of application of thermal analysis methods for quantitative analysis of composition of these mixtures.